Eksaserbasi Sedang PPOK Grup E TB Paru, Baru Terdiagnosis Klinis pada Bulan Pertama Perawatan Fase Intensif, HIV Negatif - Syazili Mustofa; Aisyah Ramadhani; Giska Tri Putri; Hendri Busman; Jordy Oktobiannobel (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder frequently associated with pulmonary tuberculosis (TB), particularly in individuals with risk factors such as smoking. We report a 65-year-old male with COPD group E who presented with dyspnea and chronic productive cough. The patient was diagnosed with newly detected pulmonary TB and was undergoing the intensive phase of anti-tuberculosis drug (OAT) therapy. Physical examination revealed bilateral wheezing with an oxygen saturation of 90%, which increased to 93% after administration of 2 L/min of supplemental oxygen; cardiac function was within normal limits. The patient received inhaled bronchodilators, intravenous methylprednisolone, levofloxacin, and OAT. After 10 days of hospitalization, dyspnea improved along with an increase in daily peak expiratory flow (PEF) values. This case highlights the importance of a multidisciplinary approach involving infection control and pharmacotherapy adjustment to achieve optimal clinical improvement in COPD patients with coexisting tuberculosis.